2021
DOI: 10.1002/lary.29990
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Invasion as an Independent Predictor of Survival in Patients of Stage III Squamous Cell Carcinoma of the Oral Tongue

Abstract: Objective: Depth of invasion (DOI) has been incorporated in the new AJCC 8th classification. However, even with this new AJCC classification stage III oral tongue squamous cell carcinoma (OTSCC) remains a heterogenous group. The study aims at finding a discreet group within stage III using DOI as a cut-off of 10 mm.Methods: The institutional database was reviewed from 2012 to 2018 for postoperative stage III OTSCC patients who subsequently received postoperative radiotherapy. Ninety-six patients matched the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…These findings suggest that CTs might promote local invasion, metastasis and progression of OSCC. In accordance with previous studies, 20–23 depth of invasion was identified as a poor prognostic factor in this patient cohort. Moreover, tumor budding, defined as the individual tumor cells or small clusters of tumor cells at the invasive tumor front, was also recognized as a poor prognostic factor, which was consistent with our previous serial studies 3,5,6 .…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that CTs might promote local invasion, metastasis and progression of OSCC. In accordance with previous studies, 20–23 depth of invasion was identified as a poor prognostic factor in this patient cohort. Moreover, tumor budding, defined as the individual tumor cells or small clusters of tumor cells at the invasive tumor front, was also recognized as a poor prognostic factor, which was consistent with our previous serial studies 3,5,6 .…”
Section: Discussionsupporting
confidence: 92%
“…From the 714 records retrieved, 621 records were found to be nonrelevant and excluded after reading the titles and abstract, thus leaving 93 titles for full-text retrieval. Of this, 76 were removed for, using non-MRI modalities for measuring DOI (n = 31),[ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 ] using MRI for measuring DOI in non-tongue carcinoma (n = 15),[ 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 ] lacking statistical details (n = 10),[ 57 58 59 60 61 62 63 64 65 66 ] using MRI for reasons other than DOI measurement (n = 7)[ 67 68 69 70 71 72 73 ] or measuring TT (n = 7),[ 74 75 76 77 78 79 80 ] not comparing MRI measured DOI (n = 5),[ 81 82 83 84 …”
Section: Resultsmentioning
confidence: 99%
“…2) The 7th American Joint Cancer Committee (AJCC) staging system reflected only tumor size and disease extent for the T classification, but DOI is newly included in the revised 8th AJCC staging system. 3) Also, because extranodal extension (ENE) is newly reflected in the N classification of 8th AJCC staging system, cases of metastatic lymph node (LN) with ENE findings have been upstaged to N2a or N3b. Accordingly, all OTSCC patients classified as stage III do not have ENE findings known as a major risk factor.…”
Section: Introductionmentioning
confidence: 99%